Developing Basic English Conversational Skills via Cooperative Learning Strategies and Realia-Based Instruction in the Community of Pandang Tak Jemu Tourism Village - Maldin, Siska Amelia; Azhar, Sarah; Teresa, Amelia; Farijis, Eric; Lim, Chealsy (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
The implementation of a community service program by lecturers from Batam Tourism Polytechnic in the Ecotourism Village of Pandang Tak Jemu aims to enhance the basic English communication skills of prospective tour guides. This initiative addresses pressing needs identified in the field, including limited vocabulary mastery, low self-confidence, and a lack of practical training. Utilizing a cooperative learning approach combined with the use of realia (authentic physical objects), the training program was designed to be interactive and contextual, incorporating activities such as role-plays, group discussions, and on-site practice within the tourist environment. The outcomes of the program demonstrated a significant improvement in participants’ speaking abilities, particularly in welcoming and providing information to foreign visitors. Beyond individual capacity building, the program also contributes to strengthening the role of the local community in community-based tourism development. Furthermore, the program exhibits potential for sustainability due to its use of relevant and easily replicable methods and learning resources that the community can independently adopt.